A PET blister sheet containing nanomaterials
By adding nanomaterials, toughening modified components and flame retardant additives to PET blister sheets, the problems of insufficient toughness and flame retardant properties of PET blister sheets are solved, significantly improving its performance and broadening the application fields.
Patent Information
- Application Number
- CN202510063557.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-01
AI Technical Summary
The existing PET blister sheets are easily brittle and broken when impacted by external forces, have poor toughness, and are prone to combustible, and have severe melting droplets, which limits its application range.
A PET blister sheet containing nanomaterial was prepared by adding nanomaterials, toughening modification components and flame retardant additives. The toughening modified components form flexible chain segments by reacting C36 dimeric acid with N,N-dimethylformamide, etc. to improve the toughness of the material; the flame retardant additives form flame retardant by reacting nanoacctolites with phenyl dichlorophosphate, etc. to improve the flame retardant performance of the material.
It significantly improves the elongation of break and the ultimate oxygen index of PET blister sheets, enhances its toughness and flame retardant properties, extends service life and broadens the application fields.
Smart Images

Figure CN119735928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of blister sheets, in particular to a PET blister sheet containing nano materials. Background Art
[0002] Blister sheet is a kind of plastic processing material. The main principle is to heat and soften the flat plastic hard sheet, then use vacuum adsorption to the mold surface, and then cool it to form. It is widely used in packaging, advertising, decoration, food, medicine and other fields. Among the many sheet materials, polyethylene terephthalate (PET) has become one of the preferred materials in the production of blister sheets due to its low cost, good chemical stability and good insulation. It is widely used in various fields.
[0003] With the development of modern industry, higher requirements are put forward for the functionality of PET blister sheets. In actual use, some large products of existing PET blister sheets are very likely to break brittlely when subjected to external impact, resulting in product rupture, which seriously affects the performance and safety of the products. This is because the ester group and the benzene ring in the PET macromolecule form a conjugated system, which increases the rigidity of the molecular chain and makes it difficult for the molecular chain to move, resulting in poor toughness of the PET blister sheet. In addition, PET materials are easy to burn, and there is a serious droplet phenomenon during the combustion process, which can easily cause the ignition of surrounding flammable materials, causing "secondary combustion" and expanding the scope and spread of the fire, which limits its application.
[0004] In order to broaden the application field of PET blister sheets, it is necessary to modify them to improve the toughness and flame retardant properties of PET blister sheets. For example, the invention patent with announcement number CN105482387B discloses a toughened modified transparent PET sheet composite material and a preparation method thereof. The invention uses thermoplastic elastomer, polycarbonate, nanomaterial and liquid polypropylene glycol ester to coordinate polyethylene terephthalate for toughening. Such synergistic effect can not only make the material toughened while maintaining the stability of material strength, rigidity and heat resistance, but also have a highly transparent effect, and can greatly reduce production costs. Therefore, the PET blister sheet can be modified by adding additives with good toughness and flame retardant properties to obtain high-performance PET blister sheets. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a PET blister sheet containing nano materials.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A PET blister sheet containing nano materials comprises the following raw materials in parts by weight: 60-80 parts of PET, 6-8 parts of toughening and modifying components, 5-7 parts of flame retardant additives, 8-12 parts of talcum powder, and 1-3 parts of lubricant.
[0007] Furthermore, the preparation method of the toughening and modifying component comprises the following steps: C 36 The dimer acid is added to N,N-dimethylformamide, mixed, 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and a catalyst are added, the system temperature is raised to 70-80°C under stirring conditions, stirred for 5-9 hours, cooled to room temperature and then discharged to obtain a toughening modified component.
[0008] Furthermore, the catalyst is any one of benzyltriethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.
[0009] It can be inferred that the principle of the above scheme is: under the action of the catalyst, C 36 The carboxyl groups in the dimer acid structure can undergo continuous ring-opening reactions with the epoxy groups in the 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane structure, and the molecular chain is continuously extended to ultimately obtain a toughening modified component.
[0010] Furthermore, the preparation method of the flame retardant additive comprises the following steps: S1: Mix the nanorectorite with deionized water, and perform ultrasonic dispersion for 25 to 35 minutes to form a uniform dispersion. Add diammonium tartrate to the dispersion. After the addition is completed, control the temperature to 50 to 60° C., keep the temperature and stir for 3 to 6 hours, filter, collect the product, and dry it to obtain the modified rectorite. S2: Ultrasonic dispersion of modified rectorite in dimethyl sulfoxide to form a uniform dispersion, and adding phenyl dichlorophosphate and accelerator to the dispersion. After the addition, the temperature is raised to 60-80°C, and the temperature is kept for 6-12 hours under continuous stirring. The solid material is separated, and the flame retardant additive is obtained after washing and drying.
[0011] Furthermore, in step S1, the average particle size of the nanorectorite is 5 μm.
[0012] Furthermore, in step S2, the promoter is any one of pyridine or triethylamine.
[0013] Furthermore, in step S2, the mass ratio of the modified rectorite to phenyl dichlorophosphate is 1:0.1-0.3.
[0014] It can be inferred that the principle of the above scheme is: in step S1, diammonium tartrate is used to perform intercalation modification on rectorite to obtain modified rectorite containing active hydroxyl groups between layers; in step S2, the hydroxyl groups in the modified rectorite can react with the phosphorus oxychloride groups in the structure of phenyl dichlorophosphate under the action of a promoter to obtain a flame retardant additive.
[0015] Furthermore, the preparation method of the PET blister sheet comprises the following steps: (1) Putting PET, toughening and modifying components, flame retardant additives, talcum powder and lubricant into a high-speed mixer, setting the stirring rate to 400-800 r / min, mixing for 20-40 minutes, and then discharging the materials to obtain a mixed material; (2) Melting and kneading the mixed material, and then extruding and granulating it to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0016] Furthermore, in step (1), the lubricant is any one of stearic acid, calcium stearate or zinc stearate.
[0017] Furthermore, in step (2), the temperature of the melt kneading is 200-220°C.
[0018] Beneficial effects of the present invention: (1) The present invention adds the prepared toughening and modifying components and flame retardant additives to the base material, so that the prepared PET blister sheet has a maximum elongation at break of 198.3% and a maximum limiting oxygen index of 33.8%. It has good toughness and flame retardant properties, effectively prolongs the service life of the PET blister sheet, and broadens its application field.
[0019] (2) The present invention prepares a toughening and modifying component as a filling and modifying agent for PET blister sheets. The toughening and modifying component contains active hydroxyl groups, which can react with the PET matrix during the melting process and introduce C into the PET molecular chain. 36 The long-chain flexible segments of fat, flexible ether bonds and highly flexible silicon-oxygen bonds in dimer acid form a PET molecular chain with a balance between rigidity and flexibility, which increases the flexibility of the molecular chain, so that the prepared PET blister sheet exhibits good toughness. In addition, the silicon element in the toughening and modification component can produce a synergistic effect with the flame retardant additive to further improve the flame retardant properties of the PET blister sheet.
[0020] (3) The present invention prepares nanorectorite loaded with nitrogen-phosphorus flame retardant as a flame retardant additive. On the one hand, after being organically modified, the nanorectorite can be evenly dispersed in the matrix, avoiding the negative impact caused by the agglomeration of the nanorectorite. In addition, the layered structure of the nanorectorite can effectively isolate heat and oxygen when the material burns, forming a physical barrier, thereby delaying or preventing the spread of flames and improving the flame retardant properties of the PET blister sheet. On the other hand, the nitrogen-phosphorus flame retardant in the flame retardant additive can further improve the flame retardant properties of the PET blister sheet, avoid the occurrence of fire, ensure the safety of the PET blister sheet in use, and thus significantly improve the application effect of the PET blister sheet in various fields.
[0021] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0023] Figure 1 This is an infrared spectrum test chart of the toughening and modifying component prepared in Example 1 of the present invention.
[0024] Figure 2 This is an infrared spectrum test chart of the flame retardant additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1 1. Preparation of toughening and modifying components C 36 Dimer acid is added to N,N-dimethylformamide, mixed, 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and benzyltriethylammonium bromide are added, the system temperature is raised to 70-80°C under stirring conditions, stirred for 5-9 hours, cooled to room temperature and then discharged to obtain a toughening modified component.
[0027] The infrared spectroscopy analysis of the toughening and modification components was performed using a TENSOR 27 Fourier transform infrared spectrometer produced by BRUKER, Germany. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of the toughening and modification component, 1750cm -1 The absorption peak of the ester group C=O appears at 3031cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 3290 cm -1 The absorption peak of hydroxyl group OH appears at 1015cm -1 The absorption peak of ether bond COC appears at 1045 cm -1 The absorption peak of Si-O appears at
[0028] 2. Preparation of flame retardant additives S1: Mix the nanorectorite with deionized water, and perform ultrasonic dispersion for 25 to 35 minutes to form a uniform dispersion. Add diammonium tartrate to the dispersion. After the addition is completed, control the temperature to 50 to 60° C., keep the temperature and stir for 3 to 6 hours, filter, collect the product, and dry it to obtain the modified rectorite. S2: Ultrasonic dispersion of modified rectorite in dimethyl sulfoxide to form a uniform dispersion, and adding phenyl dichlorophosphate and triethylamine to the dispersion. After the addition, the temperature is raised to 60-80°C, and the dispersion is kept warm for 6-12 hours under continuous stirring. The solid material is separated, and the flame retardant additive is obtained after washing and drying.
[0029] The flame retardant additives were analyzed by infrared spectroscopy using a TENSOR 27 Fourier transform infrared spectrometer produced by BRUKER, Germany. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of flame retardant additives, 3030cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appears at 1280cm -1 The absorption peak of P=O appears at 1171cm -1 The absorption peak of POC appears at
[0030] 3. Preparation of PET blister sheet (1) 60 g of PET, 6 g of toughening and modifying component, 5 g of flame retardant additive, 8 g of talc and 1 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 400 r / min, and after mixing for 20 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 200° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0031] Example 2 Preparation of PET blister sheet (1) 70 g of PET, 7 g of toughening and modifying component, 6 g of flame retardant additive, 10 g of talc and 2 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 600 r / min, and after mixing for 30 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 210° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0032] The preparation method of the toughening and modifying component and the flame retardant additive is the same as that in Example 1.
[0033] Example 3 Preparation of PET blister sheet (1) 80 g of PET, 8 g of toughening and modifying component, 7 g of flame retardant additive, 12 g of talc and 3 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 800 r / min, and after mixing for 40 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 220° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0034] The preparation method of the toughening and modifying component and the flame retardant additive is the same as that in Example 1.
[0035] Comparative Example 1 Preparation of PET blister sheet (1) 70 g of PET, 7 g of toughening and modifying component, 10 g of talc and 2 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 600 r / min, and after mixing for 30 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 210° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0036] The preparation method of the toughening and modifying component is the same as that in Example 1.
[0037] Comparative Example 2 Preparation of PET blister sheet (1) 70 g of PET, 6 g of flame retardant additive, 10 g of talc and 2 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 600 r / min, and after mixing for 30 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 210° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0038] The preparation method of the flame retardant additive is the same as that in Example 1.
[0039] Comparative Example 3 Preparation of PET blister sheet (1) 70 g of PET, 7 g of toughening and modifying component, 6 g of nanorectorite, 10 g of talc and 2 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 600 r / min, and after mixing for 30 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 210° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0040] The preparation method of the toughening and modifying component and the flame retardant additive is the same as that in Example 1.
[0041] Comparative Example 4 Preparation of PET blister sheet (1) 70 g of PET, 10 g of talc and 2 g of zinc stearate were put into a high-speed mixer, the stirring rate was set to 600 r / min, and after mixing for 30 min, the material was discharged to obtain a mixed material; (2) kneading the mixture at a temperature of 210° C., and then extruding and granulating the mixture to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
[0042] Performance testing: The PET blister sheets prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were made into samples that met the specifications, and the elongation at break of the samples was tested according to GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General Principles"; the combustion performance of the samples was tested according to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test", and the specific test results are shown in Table 1: Table 1 - Performance Test From the test results in Table 1, it can be seen that the PET blister sheets prepared in Examples 1 to 3 have good toughness and flame retardant properties; no flame retardant additives are added to the PET blister sheet prepared in Comparative Example 1, and the flame retardant properties of the PET blister sheet are poor compared with the examples; no toughening and modifying components are added to the PET blister sheet prepared in Comparative Example 2, and the toughness of the PET blister sheet is poor compared with the examples; in the PET blister sheet prepared in Comparative Example 3, nanorectorite is used to replace the flame retardant additive, and the flame retardant properties of the PET blister sheet are poor, which may be because the nanorectorite has not been organically modified and may have agglomeration in the matrix, resulting in a decrease in the performance of the PET blister sheet; no toughening and modifying components and flame retardant additives are added to the PET blister sheet prepared in Comparative Example 4, so the performance of the sample is poor.
[0043] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A PET blister sheet containing nanomaterials, characterized in that: The invention comprises the following raw materials in parts by weight: 60 to 80 parts of PET, 6 to 8 parts of toughening and modifying components, 5 to 7 parts of flame retardant additives, 8 to 12 parts of talc powder and 1 to 3 parts of lubricant.
2. The PET blister sheet containing nanomaterials according to claim 1, characterized in that: The preparation method of the toughening and modifying component comprises the following steps: C 36 The dimer acid is added to N,N-dimethylformamide, mixed, 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane and a catalyst are added, the system temperature is raised to 70-80°C under stirring conditions, stirred for 5-9 hours, cooled to room temperature and then discharged to obtain a toughening modified component.
3. The PET blister sheet containing nanomaterials according to claim 2, characterized in that: The catalyst is any one of benzyltriethylammonium bromide, tetrabutylammonium bromide or tetrabutylammonium hydrogen sulfate.
4. The PET blister sheet containing nanomaterials according to claim 1, characterized in that: The preparation method of the flame retardant additive comprises the following steps: S1: Mix the nanorectorite with deionized water, and perform ultrasonic dispersion for 25 to 35 minutes to form a uniform dispersion. Add diammonium tartrate to the dispersion. After the addition is completed, control the temperature to 50 to 60° C., keep the temperature and stir for 3 to 6 hours, filter, collect the product, and dry it to obtain the modified rectorite. S2: Ultrasonic dispersion of modified rectorite in dimethyl sulfoxide to form a uniform dispersion, and adding phenyl dichlorophosphate and accelerator to the dispersion. After the addition, the temperature is raised to 60-80°C, and the temperature is kept for 6-12 hours under continuous stirring. The solid material is separated, and the flame retardant additive is obtained after washing and drying.
5. The PET blister sheet containing nanomaterials according to claim 4, characterized in that: In step S1, the average particle size of the nanorectorite is 5 μm.
6. The PET blister sheet containing nanomaterials according to claim 4, characterized in that: In step S2, the promoter is any one of pyridine or triethylamine.
7. The PET blister sheet containing nanomaterials according to claim 4, characterized in that: In step S2, the mass ratio of the modified rectorite to phenyl dichlorophosphate is 1:0.1-0.
3.
8. The PET blister sheet containing nanomaterials according to claim 1, characterized in that: The preparation method of the PET blister sheet comprises the following steps: (1) Putting PET, toughening and modifying components, flame retardant additives, talcum powder and lubricant into a high-speed mixer, setting the stirring rate to 400-800 r / min, mixing for 20-40 minutes, and then discharging the materials to obtain a mixed material; (2) Melting and kneading the mixed material, and then extruding and granulating it to obtain a granular material; (3) The granular material is transferred to a screw extruder for melt plasticization, screw pressure conveying, extrusion, rolling traction, cooling and shaping to obtain a PET blister sheet.
9. The PET blister sheet containing nanomaterials according to claim 8, characterized in that: In step (1), the lubricant is any one of stearic acid, calcium stearate or zinc stearate.
10. The PET blister sheet containing nanomaterials according to claim 8, characterized in that: In step (2), the temperature of the melt mixing is 200-220°C.
Citation Information
Patent Citations
A toughened modified transparent PET sheet composite material and its preparation method
CN105482387B